CURRENT KNOWLEDGE ABOUT THE ETIOPATHOGENESIS AND THERAPY OPTIONS FOR COVID-19 - Pesic, Srdjan; Jovanovic, Hristina; Trajkovic, Hristina (HEALTH CARE, 2020)
Currently, over 35 million people in the world are infected with the COVID-19 and over a million have died. The pandemic character of the disease has imposed dynamic research both in the field of clarification of the etiopathogenetic mechanisms of the disease and in the field of possible therapy. The amount of scientific knowledge has increased dozens of times in the last nine months, but we are still not even close to define an effective and safe therapy. The knowledge that COVID-19 is not only a respiratory but also a multisystem disease, which affects almost all organs, gave us opportunities for therapeutic adjustments. Strong oxidative stress, silent chronic hypoxia, increased coagulability, and increased platelet aggregation are just some of the mechanisms in the development of the disease. Cardiovascular consequences and vascular endothelial dysfunction are thought to be mainly responsible for death with a dangerous cytokine storm and acute respiratory distress syndrome. Having all this in mind in the therapeutic sense, it is proposed to use antibiotics, high doses of vitamin C, blood transfusion, immunoglobulin, interferon, anti-IL-6 antibodies, small doses of dexamethasone or other corticosteroids, specific antiviral drugs such as favipiravir and remdesivir. The use of chloroquine is excluded from the therapeutic protocols of the World Health Organization and the Centers for Disease Control and Prevention (United States of America). For preventive and supportive purposes, high doses of vitamin D, vitamin C, zinc, probiotics, alpha-lipoic acid, and other supplements are recommended. The use of anti-inflammatory, analgo-antipyretics drugs is considered justified, as well as the use of small doses of acetylsalicylic acid. Over 70 other drugs are currently being tested in over 400 clinical studies. In patients who already use corticosteroids by inhalation or intranasally due to asthma, chronic obstructive pulmonary disease, allergic rhinitis, or biological drugs due to immunomodulatory inflammatory diseases, this therapy should not be changed and it is not a prerequisite condition for more severe forms of the disease. The specifics of the infection in special populations such as children or pregnant women must also be taken into consideration.